Fatigue profile among petrochemical firefighters and its relationship with safety behavior: the moderating and mediating roles of perceived safety climate. Issue 3 (3rd July 2022) - Ghasemi, Fakhradin; Zarei, Hemn; Babamiri, Mohammad; Kalatpour, Omid
Abstract : The present study aimed to investigate fatigue among firefighters and its relationship with their safety behavior. The moderation and mediation effects of perceived safety climate on this relationship were also investigated. Firefighters from 10 petrochemical companies in Iran were investigated. Moderation analysis was performed based on hierarchical regression analyses and mediation effects were studied using structural equation modeling. A total number of 261 firefighters participated in this study. The mean scores of general fatigue, physical fatigue, reduced activity, reduced motivation and mental fatigue were 10.5, 9.0, 8.2, 7.6 and 8.7, respectively. Fatigue had a negative significant effect on firefighters' safety behavior. Perceived safety climate had a mediation but not moderation effect on the relationship between fatigue and safety behavior of firefighters. Generally, the fatigue level among firefighters was fairly low, but had a significant negative effect on firefighter's safety behavior. Perceived safety climate can mediate such a negative effect.